On the transport properties of microcrystalline silicon - Fejfar, A.; Beck, N.; Stuchlíková, H.; Wyrsch, Nicolas; Torres, Pedro; Meier, Johannes; Shah, Arvind; Kočka, J. (My University, 1998)
To determine the charge collection mechanism in hydrogenated microcrystalline silicon (μc-Si:H) solar cells, we have measured the electronic transport properties of μc-Si:H by time-of-flight and by ac capacitance and conductance on a unique 5.6 μm thick sample. We found the electron drift mobility μD=2.8±0.2 cm2 V−1 s−1, thermally activated with EA=0.14±0.1 eV. Evidence for field inhomogeneity was observed as an initial maximum of the photocurrent transients and as an increase of capacitance over the geometrical value. The frequency dependence of the capacitance exhibits marked differences from a-Si:H and is proposed as a tool for studying the effects of microstructure on electronic properties. Changes of the sample capacitance with temperature and illumination were observed. As a consequence of the inhomogeneity of the material, several different activation energies were found: 0.14 eV for electron drift mobility, 0.29 eV for ac conductivity, 0.4 eV for steady state dark conductivity and finally ≥0.8 eV for the photocapacitance relaxation.
Keywords: microcrystalline silicon; charge transport; time-of-flight